THE CONTRIBUTION OF MOTIVATION LEVEL AND LANGUAGE LEARNING ENVIRONMENT TO THE SUCCESSFUL FOREIGN LANGUAGE LEARNING (Proceeding 7th International Seminar on Regional Education, 2015)
Abstrak This paper reports a biographic enquiry of two tertiary English learners from Kuantan Singingi Riau and seeks to capture the developmental processes of the learnersâ language learning approaches. By sharing their past language learning experiences, the two learners verbalized their struggles in language learning and revealed the deep impact that their learning settings had on their perceptions of self and language learning. Their adopted learning approaches, as revealed in their biographical accounts, seem to be extremely exam-oriented and are dependent on the learnersâ self-will and effort as well as teachersâ support and attention. Both learnersâ accounts suggest that their language learning approaches are influenced by the contextual discourses about learning English, stressful social processes and a sense of threatened self-identity as English major graduates in a highly competitive educational context.Key words: language learning approaches, biographic study and tertiary English learners